The analysis of foreign countries experience in information technologies application in higher education - Kotliarenko Iuliia; Kolesnichenko Alvina (SHS Web of Conferences, 2022)
This paper analyses the use and effectiveness of modern information technologies application in higher education in different countries. This form of learning needs to provide the level of knowledge and competences corresponding to the traditional learning. This article shows advantages and disadvantages of ICT usage in higher education. This article gives the relevance of the comprehensive definition of ICT and their impact on e-learning and teaching processes. The analysis of the pedagogical experience of states with a high level of technological development is interesting and relevant for educational system of Russia This paper focuses on the different models of distance education and the aim of the article is to analyse the present status of the use of digital technologies in foreign countries.